Assessing Two Measurements of Self-Control for Juvenile Delinquency in China - Weng, Xue (Journal of contemporary criminal justice, 2018)
The purpose of the present study is to examine the theoretical efficiency of Hirschi’s reconceptualization of self-control in two groups of Chinese adolescents. The study also incorporates the well-established attitudinal scale from Grasmick et al. to examine whether there are any differences in the explanatory power between the two self-control scales among a comparison group of Chinese adolescents (N = 2,048). Structural equation modeling is applied to investigate the underlying theoretical structure of the self-control construct and the robustness of the scales across diverse samples. Our results provide evidence that Grasmick’s attitudinal scale has more explanatory power than that of Hirschi’s revised measure in predicting Chinese juvenile delinquency. Both measures show a better model fit in the offender sample than in the student counterparts. Our empirical test provides solid evidence for Grasmick’s attitudinal scale as a consistent predictor of Chinese juvenile delinquency compared with Hirschi’s revised measure. Theoretical and empirical directions for future research are discussed.